2017
DOI: 10.1007/7854_2017_35
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Approaches to Neurocircuits in PTSD and TBI: Imaging the Interplay of Neural and Emotional Trauma

Abstract: Posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) commonly co-occur in general and military populations and have a number of overlapping symptoms. While research suggests that TBI is risk factor for PTSD and that PTSD may mediate TBI-related outcomes, the mechanisms of these relationships are not well understood. Neuroimaging may help elucidate patterns of neurocircuitry both specific and common to PTSD and TBI and thus help define the nature of their interaction, refine diagnostic classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…Both diseases are common; approximately 25 million Americans have PTSD and there are 2.6 million new cases of TBI annually ( http://www.cdc.gov/TraumaticBrainInjury/data/index.html ). Multiple studies have shown that TBI increases the probability of developing PTSD, yet the underlying mechanisms are unknown ( Bryant, 2011 ; Yurgil et al., 2014 ; Spadoni et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both diseases are common; approximately 25 million Americans have PTSD and there are 2.6 million new cases of TBI annually ( http://www.cdc.gov/TraumaticBrainInjury/data/index.html ). Multiple studies have shown that TBI increases the probability of developing PTSD, yet the underlying mechanisms are unknown ( Bryant, 2011 ; Yurgil et al., 2014 ; Spadoni et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The normalization to ICV also accounts for the voxel size variation. 20 Unfortunately, the number of neuroimaging studies of combat-related co-morbid mTBI and PTSD are sparse 9,21,22 . In the case of amygdala volume and PTSD, several volumetric imaging analyses have presented seemingly contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
“…This impaired response during the vulnerable post-injury period can result in loss of essential immediate anti-inflammatory actions of GC, exacerbating the chronic inflammatory state (Komoltsev and Gulyaeva, 2022 ). Additionally, survivors of TBI have an increased likelihood of developing post-traumatic stress disorder (PTSD), which can amplify the stress and trauma experienced post-TBI (Spadoni et al, 2018 ). Chronic variable stress (CVS) is frequently used to model PTSD in rodents, and CVS followed by TBI causes greater cognitive deficits than either CVS or TBI alone (Fesharaki-Zadeh et al, 2020 ).…”
Section: Tbi Induces Neuroendocrine Dysfunctionmentioning
confidence: 99%